Implementation of Enhanced Recovery After Surgery (ERAS) Protocols in Pediatric Cardiac Surgery: A Comprehensive Review - Nugroho, Edwin Rasendriya; Heroe Soebroto; Ketut Alit Utamayasa (Talenta Publisher, 2026)
Background: Enhanced Recovery After Surgery (ERAS) represents an evidence-based, multidisciplinary approach that optimizes perioperative care, reduces surgical stress, and accelerates postoperative recovery. While ERAS protocols have been widely implemented in adult cardiac surgery, their adaptation to pediatric congenital heart disease (CHD) remains emerging and underexplored. Pediatric populations pose unique challenges due to differences in physiology, surgical complexity, and developmental status. Objectives: This review aims to provide a comprehensive overview of ERAS implementation in pediatric cardiac surgery, focusing on its key components, outcomes, and research gaps to guide future practice and investigation. Methods: A narrative literature review was conducted using PubMed and Google Scholar, targeting publications from 2010 to 2025. The search utilized the keywords “Enhanced Recovery After Surgery,” “ERAS,” “Pediatric Cardiac Surgery,” and “Congenital Heart Disease.” Relevant randomized controlled trials, cohort studies, reviews, and clinical guidelines were critically analyzed to identify core ERAS elements, perioperative strategies, and reported outcomes. Discussion: The reviewed evidence supports that ERAS protocols in pediatric cardiac surgery are feasible and associated with reduced mechanical ventilation duration, ICU stay, and hospital length of stay, without increasing complications or readmissions. However, most available studies are observational, highlighting the scarcity of randomized controlled trials specifically addressing pediatric CHD. Conclusion: ERAS offers a promising framework to enhance recovery and safety in pediatric cardiac surgery. Standardized, multicenter trials are required to establish evidence-based pediatric ERAS models and determine their long-term impact on recovery and quality of life. Keyword: cardiac surgery, congenital heart disease, ERAS, pediatric, recovery Latar Belakang: Enhanced Recovery After Surgery (ERAS) merupakan pendekatan multidisiplin berbasis bukti yang bertujuan mengoptimalkan perawatan perioperatif, mengurangi stres pembedahan, dan mempercepat pemulihan pascaoperasi. Meskipun protokol ERAS telah banyak diterapkan pada pembedahan jantung dewasa, adaptasinya pada kasus Congenital Heart Disease (CHD) pediatrik masih tergolong baru dan belum banyak diteliti. Populasi pediatrik memiliki tantangan tersendiri karena perbedaan fisiologi, kompleksitas pembedahan, serta status perkembangan. Tujuan: Tinjauan ini bertujuan untuk memberikan gambaran komprehensif mengenai penerapan ERAS pada pembedahan jantung pediatrik, dengan menyoroti komponen utama, luaran klinis, serta kesenjangan penelitian untuk panduan praktik dan penelitian selanjutnya. Metode: Tinjauan literatur naratif dilakukan dengan menggunakan basis data PubMed dan Google Scholar untuk publikasi tahun 2010 hingga 2025. Pencarian dilakukan dengan kata kunci “Enhanced Recovery After Surgery,” “ERAS,” “Pediatric Cardiac Surgery,” dan “Congenital Heart Disease.” Artikel yang relevan, termasuk randomized controlled trials, studi kohort, tinjauan pustaka, dan pedoman klinis dianalisis secara kritis untuk mengidentifikasi elemen utama ERAS, strategi perioperatif, serta luaran yang dilaporkan. Pembahasan: Bukti yang ditinjau menunjukkan bahwa penerapan protokol ERAS pada pembedahan jantung pediatrik bersifat layak dan berhubungan dengan penurunan durasi ventilasi mekanik, lama perawatan di ICU, serta lama rawat inap, tanpa meningkatkan komplikasi maupun angka readmisi. Namun, sebagian besar studi yang tersedia bersifat observasional, menyoroti keterbatasan uji acak terkontrol yang secara khusus meneliti CHD pediatrik. Kesimpulan: ERAS menawarkan kerangka kerja yang menjanjikan untuk meningkatkan pemulihan dan keamanan pada pembedahan jantung pediatrik. Diperlukan uji multicenter terstandar untuk membangun model ERAS berbasis bukti pada populasi pediatrik serta menilai dampak jangka panjangnya terhadap pemulihan dan kualitas hidup. Keyword: bedah jantung, ERAS, pediatrik, pemulihan, penyakit jantung bawaan